PROBLEMATIKA PENDIDIKAN ISLAM DI INDONESIA: KAJIAN KURIKULUM LEMBAGA PENDIDIKAN ISLAM - Wahid, Abdul; Amrin, Amrin; Supriyanto, Supriyanto (Ibn Khaldun University, Bogor, 2022)
The purpose of this research is to reveal the problems of Islamic education in Indonesia to find out what problems exist in Islamic education itself. Currently, there are so many problems or problems faced by the government, society and Islamic EducationalInstitutions. One of these problems is the curriculum problem at the Islamic Education Institute. Curriculum issues must also receive clear and directed handling from the government and related institutions. Handling these problems is one solution that can improve Islamic education in Indonesia. Thus, it is hoped that Islamic education in Indonesia will be better, more advanced and more focused, especially in facing all kinds of challenges in this increasingly modern and more advanced era.